If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + 2(3w + 2k) + -2k = 0 Reorder the terms: 3w + 2(2k + 3w) + -2k = 0 3w + (2k * 2 + 3w * 2) + -2k = 0 3w + (4k + 6w) + -2k = 0 Reorder the terms: 4k + -2k + 3w + 6w = 0 Combine like terms: 4k + -2k = 2k 2k + 3w + 6w = 0 Combine like terms: 3w + 6w = 9w 2k + 9w = 0 Solving 2k + 9w = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-9w' to each side of the equation. 2k + 9w + -9w = 0 + -9w Combine like terms: 9w + -9w = 0 2k + 0 = 0 + -9w 2k = 0 + -9w Remove the zero: 2k = -9w Divide each side by '2'. k = -4.5w Simplifying k = -4.5w
| 9x+1-6x+5=30 | | x^2=18x+40 | | 3x+7=-29 | | -114-10x=54+4x | | 3x+2x+6=31 | | -3(x+6)=5-(-3) | | 26=4x-6 | | 8x+9=2x-15 | | onethird(6x-9)=5x+2(x+9) | | 6v*4h+2v-h=77 | | 5m+3(4)=22 | | 3a-2=19 | | -16+9x=5x+-30 | | M-3x=2x | | -5x-16=-7x+26 | | -8r=-8r-5r | | -5(x+5)=4-(-3) | | -8r=-8r-5 | | 7w-8w=-4-30 | | 10(2x-1)+5(4x+3)=-115 | | 24=5-(3-2m) | | 3x^2+63=30x | | 12y-7y+2y= | | 5-k=11-k | | 3(3)-4y=7 | | -(4y+2)-(-3y-4)=-4 | | 12x+60=13x+2 | | 8y(8+6y)=20 | | 12x-8=3x-35 | | 5x=3(x+3) | | 54x+14=43x+14 | | 7-3(2x-5)=5(3x+4)+2x |